The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/0284186x.2014.948061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of patients receiving palliative chemo- and radiotherapy during end of life at a regional cancer center in Norway

Abstract: Background. Many cancer patients receive chemotherapy and radiotherapy their last 30 days [end of life (EOL)]. The benefi t is questionable and side effects are common. The aim of this study was to investigate what characterized the patients who received chemo-and radiotherapy during EOL, knowledge that might be used to improve practice. Methods. Patients dead from cancer in 2005 and 2009 were analyzed. Data were collected from hospital medical records. When performance status (PS) was not stated, PS was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 24 publications
9
54
6
Order By: Relevance
“…In this study, 15% who died within 1 month after inclusion received chemotherapy, relative to 10% and 18% in other studies 30 33. These numbers still indicate a need for discussion and a potential for improvement.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, 15% who died within 1 month after inclusion received chemotherapy, relative to 10% and 18% in other studies 30 33. These numbers still indicate a need for discussion and a potential for improvement.…”
Section: Discussioncontrasting
confidence: 58%
“…However, the use of anti-neoplastic therapy in an acute PCU was investigated26 and it was concluded that this was limited to a small percentage of patients and was associated with characteristics such as younger age, female sex and cancer diagnoses, similar to findings in a Norwegian study 30…”
Section: Discussionmentioning
confidence: 71%
“…Given that short-course PRT regimens with no or minimal side effects exist, which nevertheless often improve symptoms, clinicians are afraid of withholding a meaningful therapeutic measure. In agreement with our findings [2], Anshushaug et al also reported that ECOG PS 3-4 was strongly associated with PRT during the last month of life [4], but other factors also play a role. Given consistent reports from different countries, should we regard 30DM of 615% as unavoidable and acceptable?…”
Section: To the Editorsupporting
confidence: 92%
“…In this regard, Anshushaug et al (19) also observed that ECOG PS 3/4 was strongly associated with palliative radiotherapy during the last month of life. The impact of performance status as a prognostic factor in patients with brain metastases is well known (20).…”
Section: Discussionmentioning
confidence: 94%